Preventive Dietary Knowledge to Combat Non-Communicable Diseases: A descriptive study contextualized Bangladeshi Female University Students (Indian Journal of Public Health Research & Development, 2025)
Non-communicable diseases (NCDs) represent one of the most pressing and intricate public health issues. This study aimed to verify the dietary knowledge of female university students regarding NCDs. This was a descriptive type of cross-sectional study with 385 female university students of Dhaka, Bangladesh. Data were gathered by pre-tested and semi-structured questionnaires. Analysis was performed by using multivariate techniques followed by regression modeling. This study reflected that the majority of the female students belonged to the age group
Keywords: Non-communicable diseases, NCDs, Preventive Dietary Knowledge